A new assessment method of sustainable water resources utilization considering fairness-efficiency-security: A case study of 31 provinces and cities in China. (June 2022) - Li, Donglin; Zuo, Qiting; Zhang, Zhizhou
Highlights: An evaluation method for SWRU was developed based on water ecological footprint model. Assessing the performance of SWRU in terms of fairness, efficiency and security. WSUI was at a relatively unsustainable level in China over the period 2005-2019. Low water resources efficiency is the most prominent factor limiting SWRU. Findings can provide scientific reference for improving regional water resources sustainability. Abstract: Accurate assessment of sustainable water resources utilization (SWRU) is one of the basis for alleviating the growing human-water conflict. However, there are some unavoidable defects in previous research, such as poor holistic considerations, subjectivity in judgment process and limited methodological applicability. Therefore, after determining the triple attributes of SWRU (i.e., fairness, efficiency and security), Gini coefficient, data envelopment analysis (DEA) technique and water ecological footprint (WEF) model were used to establish water resources fairness index (WFI), water resources efficiency index (WEI) and water resources ecological security index (WESI). The three indices were then integrated into water resources sustainable utilization index (WSUI) with Euclidean distance, thus forming the SWRU quantification method system, which can effectively overcome the above shortcomings. Finally, the temporal and spatial characteristics of SWRU during 2005-2019 were diagnosed in 31 provinces and cities of China. Results reveal that: (1) Over half of provinces have a mismatch between population and water distribution, especially in the north, where the contradiction of more people and less water is chronic; (2) The decline in water resources efficiency has not attracted sufficient attention for a long time; (3) WESI in the south was below threshold 1 and water resources ecology is safe, while the northern regions are basically at an insecure level; (4) WSUI multi-year average was within [0.44, 0.51] in China, which has been at relatively unsustainable level, and low water resources efficiency is the most prominent factor limiting SWRU. These findings can provide scientific reference for improving the sustainable utilization of regional water resources.